2011
DOI: 10.1179/joc.2011.23.6.358
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRIChemotherapy in Patients with Advanced Non Resectable Esophageal or Junctional Adenocarcinoma: A Pilot Study

Abstract: In this prospective pilot study, we assessed the efficacy and safety of the FOLFIRI regimen (irinotecan 180 mg/m², leucovorin 200 mg/m² d1 followed by bolus 400 mg/m² 5-fluorouracil (5-FU) and by a 46-h 2400 mg/m² 5-FU infusion, every 2 weeks) in patients with advanced esophageal or junctional adenocarcinoma. Twenty-nine patients were included. A complete response was obtained in 2 patients, a partial response in 7 patients (objective response rate 31.0%). Stable disease was obtained in 13 patients (disease co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…5‐fluorouracil (5‐FU) was the first‐line treatment for ESCC therapy for several decades (Longley et al., 2003), but single agent chemotherapy of 5‐FU is no longer appropriate for ESCC therapy because of its toxicity, drug resistance, and side effects. Therefore, the development of combination therapies with other drugs, such as irinotecan and oxaliplatin, is used to improve prognoses and reduce the side effects of 5‐FU (Ferte et al., 2011; Wainberg et al., 2011). Combination therapy enhances the response rate and survival rate, but the side effects and drug resistance are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…5‐fluorouracil (5‐FU) was the first‐line treatment for ESCC therapy for several decades (Longley et al., 2003), but single agent chemotherapy of 5‐FU is no longer appropriate for ESCC therapy because of its toxicity, drug resistance, and side effects. Therefore, the development of combination therapies with other drugs, such as irinotecan and oxaliplatin, is used to improve prognoses and reduce the side effects of 5‐FU (Ferte et al., 2011; Wainberg et al., 2011). Combination therapy enhances the response rate and survival rate, but the side effects and drug resistance are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, the serious issue of irinotecan in clinical practice was its dose-limiting toxicity, including severe neutropenia, regardless of any cancers. [1][2][3] Irinotecan is also a potent inhibitor of topoisomerase I, is initially hydrolyzed to its active metabolite 7-ethyl-10-hydroxycamptothecin (SN-38), which is then subsequently inactivated through UGT1A1-mediated glucuronidation. [4] Irinotecan-induced neutropenia is a complex, polygenic phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…However, the serious issue of irinotecan in clinical practice was its dose-limiting toxicity, including severe neutropenia, regardless of any cancers. [1–3]…”
Section: Introductionmentioning
confidence: 99%
“…UGT1A1 has genomic polymorphisms such as UGT1A1*28 and *6. It has been found that UGT1A1*28 and UGT1A1*6 were associated with irinotecan-induced severe toxicity in advanced colorectal cancer (Toffoli et al 2006;Xu et al 2016), but this conclusion is still controversial due to the different frequencies of UGT1A1 genotypes in eastern and western countries (Ferte et al 2011;Kaya et al 2012). More importantly, in the Chinese population, the association between UGT1A1*6/*28 polymorphism and irinotecan-induced toxicity and e cacy of advanced gastric cancer is rarely reported.…”
Section: Introductionmentioning
confidence: 99%